Chemical investigations for extraction, identification an de termination of . the poisons from animals' vicera that poisoned experimentally with carbamate groubs pecticides - H. Alırnet ACET (Eurasian Journal of Veterinary Sciences)
It is fact that agricultural drugs, especially pesticides: have been used unconsciously in the regions where intensive agriculture is made in this country. Carbamate pecticides of these were studied ta determine under our laboratory conditions. The identifications of carbaryl, baygon, mesurol, methomyl, matacil: primicarbe and promecarbe of carbamate pecticides were made witb thin-layer chromatograms. The spoted layers were developed with ten different solvent systems. Dibromoquinonchlorimide, ninhydrin, rhodamin B, rhodamin B- AgN03, bromin- fluorescein reagents and UV light with short wave (254 ıim) were used to determine the spots on the developed layers. The sensitivitiy limits_and the color reactions of seven various carbamate pecticide.s were also determined with the aid of this reagents. Carbaryl, baygon- and carbaryl+ baygon mixture were given orally to ten rabbits and three dogs in LD50 doses. After adınİnistering of the drugs was seen that all animals were died. Stomach in testine, li ver, kidney and spleen of these animals were removed. After the results of our research was detern1inde the above sfated chemical compounds in this organs. Carbamate pecticides were determinde at the levels of 0,5 µg or more with the aid of dibromoquinonchlorimid in this tissues samples on this laboratory conditions.